The Trumpet Sounds, But for Who? A Survey of Contemporary Applications of the Biblical Jubilee - Christopher James Luthy (Sekolah Tinggi Theologia Jaffray, 2023)
Since the middle of the twentieth century, the biblical Jubilee has enjoyed an increasing level of prominence in the public sphere. It has been cited as the basis for a number of different movements, traditions and practices, many of which vary greatly in their emphases. This qualitative study surveys and critically analyses each of the major contemporary applications of the biblical jubilee, as represented in the current corpus of academic literature. It is concluded that these applications can be categorised under eight headings. It is also concluded that the significant variation in many of these applications is the product of a variety of hermeneutical approaches. The validity of these approaches and an assessment of the varying applications is to be the subject of future study.